2017
DOI: 10.1136/bmjdrc-2017-000438
|View full text |Cite|
|
Sign up to set email alerts
|

Statin use and risk of developing diabetes: results from the Diabetes Prevention Program

Abstract: ObjectiveSeveral clinical trials of cardiovascular disease prevention with statins have reported increased risk of type 2 diabetes (T2DM) with statin therapy. However, participants in these studies were at relatively low risk for diabetes. Further, diabetes was often based on self-report and was not the primary outcome. It is unknown whether statins similarly modify diabetes risk in higher risk populations.Research design and methodsDuring the Diabetes Prevention Program Outcomes Study (n=3234), the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
2
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 31 publications
6
72
2
8
Order By: Relevance
“…However, this is a pleiotropic class of drugs that also exerts several anti-inflammatory effects (43, 544). Despite these anti-inflammatory effects, several studies have now shown statin use to be associated with an increased risk for T2DM (89, 91, 381, 410). Furthermore, results from Cederberg et al suggest that statins reduce insulin sensitivity and insulin secretion (63).…”
Section: Adipose Tissue Inflammation and Insulin Resistancementioning
confidence: 99%
“…However, this is a pleiotropic class of drugs that also exerts several anti-inflammatory effects (43, 544). Despite these anti-inflammatory effects, several studies have now shown statin use to be associated with an increased risk for T2DM (89, 91, 381, 410). Furthermore, results from Cederberg et al suggest that statins reduce insulin sensitivity and insulin secretion (63).…”
Section: Adipose Tissue Inflammation and Insulin Resistancementioning
confidence: 99%
“…However, older adults with diabetes may find adherence to statin therapy challenging due to many reasons, including polypharmacy, increased susceptibility to adverse events, and as a result of declining executive and cognitive functioning . There is strong evidence linking statins with increased risk of diabetes . Furthermore, among people with established diabetes, statin therapy has been associated with poor glycemic control, which could contribute to increased discontinuation or poor adherence.…”
Section: Introductionmentioning
confidence: 99%
“…17 There is strong evidence linking statins with increased risk of diabetes. 18 Furthermore, among people with established diabetes, statin therapy has been associated with poor glycemic control, 19 which could contribute to increased discontinuation or poor adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Several years ago, it was revealed that statins, widely used for LDL lowering, are associated with a slightly higher risk of diabetes [2,3,4▪]. This risk is statin dose-dependent [5].…”
Section: Introductionmentioning
confidence: 99%